Complete mitochondrial genome and phylogenetic analysis of a Chorthippus fallax (Zuboxsky) isolated in rangeland of northwest region of China - Jialu Deng; Ziqi Yu; Jie Ning; Heng Wang; Xinda Lin; Xiaoli Liu (Mitochondrial DNA. Part B. Resources, 2020)
In this study, we assembled a complete 16,143 bp mitochondrial genome for Chorthippus fallax (Zuboxsky), which encodes 13 protein-coding genes, 22 tRNAs, 12S and 16S rRNAs and a 722 bp D-loop in the characteristic arrangement of superfamily Acrididae. The most common start codon for 13 PCGs is ATG and the most common termination codon is TAA. The overall A + T content was 75.13%. Phylogenetic analysis based on the entire mitochondrial genome indicated C. fallax (Zuboxsky) had more close relationship with Euchorthippus fusigeniculatus and Chorthippus chinensis in family Arcypteridae, and implied non-monophyly for the family. The data will be important for better understanding of the phylogenetic relationship of members in Acrididae superfamily.